2016
DOI: 10.3389/fpsyg.2016.00007
|View full text |Cite
|
Sign up to set email alerts
|

Increased Event-Related Potentials and Alpha-, Beta-, and Gamma-Activity Associated with Intentional Actions

Abstract: Objective: Internally guided actions are defined as being purposeful, self-generated and offering choices between alternatives. Intentional actions are essential to reach individual goals. In previous empirical studies, internally guided actions were predominantly related to functional responses in frontal and parietal areas. The aim of the present study was to distinguish event-related potentials and oscillatory responses of intentional actions and externally guided actions. In addition, we compared neurobiol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
81
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 53 publications
(84 citation statements)
references
References 96 publications
(147 reference statements)
3
81
0
Order By: Relevance
“…Interestingly, they note that the product method appeared to remain unaffected by right censoring, while the difference method underestimated the indirect effect in their simulation studies. 16 The results of our paper will provide the theoretical underpinning for the conclusions drawn from simulation studies by Tein and MacKinnon 9 and Gelfand et al 16 . We supply formal justification for their conjecture that the difference method will often fail to provide a consistent estimator of the indirect effect under an accelerated failure time model even when the product method does.…”
Section: Introductionmentioning
confidence: 60%
See 2 more Smart Citations
“…Interestingly, they note that the product method appeared to remain unaffected by right censoring, while the difference method underestimated the indirect effect in their simulation studies. 16 The results of our paper will provide the theoretical underpinning for the conclusions drawn from simulation studies by Tein and MacKinnon 9 and Gelfand et al 16 . We supply formal justification for their conjecture that the difference method will often fail to provide a consistent estimator of the indirect effect under an accelerated failure time model even when the product method does.…”
Section: Introductionmentioning
confidence: 60%
“…They cautioned that the estimated direct and indirect effects for a Cox proportional hazards model are based on a rare disease assumption, while the accelerated failure time model does not require such an assumption. 15 In a more recent paper, Gelfand et al 16 encourage the use of accelerated failure time models over Cox proportional hazards models in mediation analysis. A commonly noted drawback of the accelerated failure time model is that the event times are assumed to follow a specific distribution, but Gelfand et al 16 argue that the breadth of distributions available can capture the variability in survival data, and the Weibull distribution can represent distributions commonly found in clinical research.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One study compared a working memory intervention incorporating verbal and visuospatial training versus a group CBT intervention in adolescents aged 11-14 with high anxiety and low attentional control. Overall, both groups showed improvements in anxiety symptoms, increased inhibitory control, and reduced attentional biases to threat at post-treatment with the working memory group demonstrating superior performance to the CBT group on working memory tasks[90]. The authors cite these findings as evidence that working memory training has similar advantages to traditional CBT[90].…”
Section: Anxiety Disordersmentioning
confidence: 99%
“…Overall, both groups showed improvements in anxiety symptoms, increased inhibitory control, and reduced attentional biases to threat at post-treatment with the working memory group demonstrating superior performance to the CBT group on working memory tasks[90]. The authors cite these findings as evidence that working memory training has similar advantages to traditional CBT[90]. By contrast, Wanmaker et al[91] found that an adaptive working memory training was not beneficial in improving anxiety, depressive, and ruminative symptoms in anxious and depressed patients.…”
Section: Anxiety Disordersmentioning
confidence: 99%